Rocking the Boat but Keeping It Steady: The Role of Emotion Regulation in Employee Voice - Grant, Adam M. (Academy of Management Journal, 2013)
Intense emotions such as frustration, anger, and dissatisfaction often drive employees to speak up. Yet the very emotions that spur employees to express voice may compromise their ability to do so constructively, preventing managers from reacting favorably. I propose that to speak up frequently and constructively, employees need knowledge about effective strategies for managing emotions. Building on theories of emotion regulation, I develop a theoretical model that explains the role of managing emotions in the incidence and outcomes of voice. In a field study at a health care company, emotion regulation knowledge (1) predicted more frequent voice, (2) mediated by the emotional labor strategies of deep acting and surface acting, and (3) enhanced the contributions of voice to performance evaluations. These results did not generalize to helping behaviors, demonstrating that emotion regulation uniquely affects challenging but not affiliative interpersonal citizenship behaviors. This research introduces emotion regulation as a novel influence on voice and its consequences.